My brother - Browne, Anthony, 1946- (London : Picture Corgi, 2009)
A child describes the many wonderful things about "my brother," who can fly, write amazing stories, and stand up to bullies.
K-3.
K-3
English.
Keywords: Brothers -- Juvenile fiction; Brothers -- Fiction; Brothers -- Fiction